Mechanisms Of Fair Value Measurement Of Long-Term Assets In Business Entities (American Economist: Journal of Economics Finance and Global Policy, 2026)
The article analyzes the mechanisms of fair value measurement of longterm assets based on international standards (IFRS 13, IAS 16, IAS 36, IAS 38). According to the 2022–2025 dynamics, buildings and land showed stable growth under the market approach, intangible assets demonstrated high relative differences under the income approach, while equipment revealed declines through impairment testing. National practice issues and solutions for harmonization are discussed. Ultimately, applying fair value ensures transparency and reliability of financial statements and enhances investment attractiveness.
Keywords: Fair value; long-term assets; international standards